Oxygen Management During Collective Aeromedical Evacuation of 36 COVID-19 Patients With ARDS. Issue 7 (1st July 2021) - Beaussac, Madeleine; Boutonnet, Mathieu; Koch, Lionel; Paris, Raphael; Di Filippo, Julia; Distinguin, Berangère; Murris, Sophie; Dupre, Henri-Louis; Muller, Violaine; Turc, Jean
Abstract: Objective: The ongoing coronavirus disease-2019 pandemic leads to the saturation of critical care facilities worldwide. Collective aeromedical evacuations (MEDEVACS) might help rebalance the demand and supply of health care. If interhospital transport of patients suffering from ARDS is relatively common, little is known about the specific challenges of collective medevac. Oxygen management in such context is crucial. We describe our experience with a focus on this resource. Methods: We retrospectively analyzed the first six collective medevac performed during the coronavirus disease-2019 pandemic by the French Military Health Service from March 17 to April 3, 2020. Oxygen management was compliant with international guidelines as well as aeronautical constraints and monitored throughout the flights. Presumed high O2 consumers were scheduled to board the last and disembark the first. Results: Thirty-six mechanically ventilated patients were successfully transported within Europe. The duration of onboard ventilation was 185 minutes (145-198.5 minutes), including the flight, the boarding and disembarking periods. Oxygen intake was 1, 650 L per patient per flight (1, 350-1, 950 L patient per flight) and 564 L per patient per hour (482-675 L per patient −1 per hour) and surpassed our anticipation. As anticipated, presumed high O2 consumers had a reduced ventilation duration onboard. The estimations of oxygen consumptions were frequently overshot, and only two hypoxemia episodes occurred. Conclusion: Oxygen consumption was higher than expected, despite anticipation and predefined oxygen management measures, and encourages to a great caution in the processing of such collective medevac missions.